National Trends and Cost of Minimally Invasive Surgery in Urology. Issue 2 (March 2015) - Chughtai, Bilal; Scherr, Douglas; Del Pizzo, Joseph; Herman, Michael; Barbieri, Christopher; Mao, Jialin; Isaacs, Abby; Lee, Richard; Te, Alexis E.; Kaplan, Steven A.; Schlegel, Peter; Sedrakyan, Art
Abstract : Introduction: : We determine national trends in costs of care as well as associated growth and adoption of minimally invasive surgery for major uro‐oncology procedures. Methods: : Using a nationally representative sample we identified patients diagnosed with prostate, renal and bladder cancer who underwent prostatectomy, nephrectomy, partial nephrectomy and cystectomy from 2000 to 2011. Temporal trends in patient demographics, hospital and procedure related characteristics, surgical volume, minimally invasive surgery use and costs of hospitalization over the years were analyzed. Hierarchical linear regression was performed to evaluate the effects of hospital volume, time and surgery type on costs of hospitalization. Results: : Overall 836, 563, 440, 337 and 122, 992 patients underwent prostatectomy, nephrectomy and cystectomy from 2000 to 2011, respectively. There was a 33.6%, 50.8% and 25.5% increase in annual surgical volume for these 3 surgeries during the 10 years, with the most prominent increase at high volume hospitals. The use of minimally invasive surgery increased 65.6% for prostatectomy, 22.0% for nephrectomy and 12.5% for cystectomy, and this increase was more prominent at high volume hospitals. For all 3 surgeries the hospital stay for minimally invasive surgery cases was more expensive than for open procedures, but decreased during the study period from 17, 367 to 11, 145 for prostatectomy and from 54, 209 to 28, 753 for cystectomy. Conclusions: : High volume hospitals experienced greater growth in surgery caseloads and minimally invasive surgeries but this did not lead to higher costs of care. While minimally invasive surgery has consistently been more expensive than open surgery, the costs of minimally invasive prostatectomy and cystectomy have decreased in the last decade.